Socialization, Implementation of Samsat Drive Thru and Motor Vehicle Taxpayer Compliance - Herdianto Gurning; P.D’Yan Yaniartha Sukartha (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
This study analyzes Motor Vehicle Taxpayer Compliance in Gianyar Regency based on data that motor vehicles are increasing every year but the tax revenue target fluctuates. The purpose of this study is to determine and obtain empirical evidence whether the socialization and application of samsat drive thru affects the compliance of motor vehicle taxpayers. This study used two independent variables, namely tax socialization and samsat drive thru. This study used a quantitative approach in associative form. This study used one hundred respondents using the slovin formula with metode incidental sampling. The data analysis technique used is multiple linear analysis. The results showed that the tax socialization variable had an effect on motor vehicle taxpayer compliance, and the drive thru samsat variable had no effect on motor vehicle taxpayer compliance in Gianyar Regency. Tax socialization encourages people to pay vehicle taxes, while samsat drive thru does not increase public interest in paying motor vehicle taxes.